2018
DOI: 10.21608/jvmr.2018.43298
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of the oviduct in Egyptian Balady Duck (Anas boschas domesticus) during laying cycle.

Abstract: The objective of the current study was to present baseline data on the morphology and surface architecture of the oviduct in adult female Balady duck grossly and by using scanning electron microscope (SEM). Fifteen apparently healthy adult female Balady ducks were used which weighted (2-4 kg). Two birds were formalized while the other birds were used in the fresh state for dissection then careful evisceration of the oviduct. For SEM five of the latter were used immediately after immersion in saline. Our data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…The uterus of both Indigenous chicken of Assam and Kamrupa variety was the dilated muscular portion of the oviduct with visible longitudinal folds internally, which were in concurrence with W ani et al (2017) in native chicken of Kashmir and Mahmoud et al (2018) in Egyptian Balady Duck. The mean length of the uterus in the indigenous chicken of Assam and Kamrupa variety during different stages of laying was in concurrence with the findings of Mahmoud et al (2018) who reported that the uterus measured about 4-9 cm during laying in Egyptian Balady duck. Mishra et al (2014) also reported that the length and weight of uterus was 6.10±2.80 cm and 6.80±1.32 gm respectively at 8-11 months old chicken.…”
Section: Nssupporting
confidence: 89%
See 4 more Smart Citations
“…The uterus of both Indigenous chicken of Assam and Kamrupa variety was the dilated muscular portion of the oviduct with visible longitudinal folds internally, which were in concurrence with W ani et al (2017) in native chicken of Kashmir and Mahmoud et al (2018) in Egyptian Balady Duck. The mean length of the uterus in the indigenous chicken of Assam and Kamrupa variety during different stages of laying was in concurrence with the findings of Mahmoud et al (2018) who reported that the uterus measured about 4-9 cm during laying in Egyptian Balady duck. Mishra et al (2014) also reported that the length and weight of uterus was 6.10±2.80 cm and 6.80±1.32 gm respectively at 8-11 months old chicken.…”
Section: Nssupporting
confidence: 89%
“…This was in accordance with Dyce et al (1987) andWani et al (2017) in native chicken of Kashmir. The magnum of Egyptian Balady duck was the longest thick and creamy part of the oviduct which was convoluted and attached by dorsal and ventral oviductal ligament with average length of about 15-25 cm (Mahmoud et al, 2018). The present study revealed that the length of the magnum was significantly higher (p<0.01) during the laying period in comparison to the post-laying period in both the groups which might be due to functional inactivity of the organ.…”
Section: Resultssupporting
confidence: 41%
See 3 more Smart Citations